Hemangiomas of the liver: A propósito de 5 casos resecados - Praderi, José A; Juambeltz, Carlos; Cassinasco, Angeles; Cartazzo, José; de Mello, Washington; Bonilla, Nebel; Odriozola, Martín; Secondo, Gerardo; Praderi, Raúl (Cirugía del Uruguay, 1991)
Five cases of cavernous hepatic hemangioma treated by resection are presented. Left hepatectomy was performed in two cases, 11 and 1/lrd segmentectomy in two cases and V and Vlth segmentectomy in one case. The evolution was good. One patient suppurated. No operative morta/ity was registered.